On the irreversibility of ﬂuctuations - Sitenko, A.G. (Condensed Matter Physics, 2000)
Interrelationship of classical and quantum ﬂuctuations is discussed. With energy dissipation being taken into account, ﬂuctuations are shown to be irreversible even in the case of classical systems. An analogy to Kubo relation for classical ﬂuctuations is derived. Fluctuations in both equilibrium and nonequilibrium (though stationary) states of the system are considered.